Green wave-based virtual traffic light management scheme with VANETs. (2017) - Chou, Li-Der; Shen, Tsung-Yi; Tseng, Chia-Wei; Chang, Yao-Jen; Kuo, Yen-Wei
Green intelligent transportation systems (GITS) have received significant attention in recent years. Traffic congestion, which is an important research topic on intelligent transportation systems (ITS), is rapidly becoming one of the most serious problems affecting urban areas. This study utilises the vehicular ad hoc networks (VANETs) technology to build a virtual traffic light (VTL) environment to reduce traffic congestion. The objective of this study is to adjust the traffic light signal time length on-demand to enable vehicles to pass through numerous intersections rapidly, thereby saving energy and reducing fuel consumption. The traffic phase combination algorithm and VTL operation mechanism are also addressed to improve the traffic congestion situation in urban areas. Simulation results indicate that the proposed scheme can increase the percentage of traffic flow and the average speed of all vehicles in all intersections, thereby saving energy.